Analysis of Dialysate pH and Temperature Stability on Hemodialysis Machines Using Internet of Thing Technology - Noviyanto Putera P; Lusiana Lusiana; Endang Dian Setioningsih; Sari Luthfiyah; Abhilash Pati (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2023)
Therapy for kidney replacement with hemodialysis is a treatment that is carried out in patients with Chronic Kidney Failure to survive. The purpose of this study was to determine the stability of the dialysate fluid in the hemodialysis machine by measuring the temperature using the DS18B20 sensor and measuring the dialysate pH using the 4502C sensor on pre and post-hemodialysis. The research method and the manufacture of this module use a pre-experimental research design with the type of research